2022
DOI: 10.24252/alami.v6i1.27001
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pemberian Air Susu Ibu (Asi) Dengan Angka Kejadian Infeksi Saluran Pernapasan Akut (Ispa) Pada Balita Usia 6-12 Bulan

Abstract: Angka peristiwa infeksi saluran pernapasan akut (ISPA) di Indonesia tercatat kurang lebih 6 juta kasus pada bayi sehingga menempati urutan ke-6 dunia. WHO mencatatkan insiden ISPA pada negara berkembang kelahiran hidup bayi 15-20% dengan kematian 40/1000 pertahun pada bayi. Tujuan: untuk mengetahui korelasi pemberian air susu ibu (ASI) dengan angka kejadian infeksi saluran pernapasan akut (ISPA) pada bayi usia 6-12 bulan. Metode: menggunakan observasional analitik dengan metode cross sectional. Sampel yang dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Another research conducted by Andi Elsa Mulya Pratiwi in 2022, it was found that the relationship history of exclusive breastfeeding with the number of the incidence of ARI in infants at the Balangnipa Sinjai Health Center using the test Chi Square obtained the probability value (p-value) Chi Square of 0.000. These results show that the probability value is <0.05, thus H0 rejected while H1 is accepted so that it is stated that there is a significant relationship between history of exclusive breastfeeding and the incidence of urinary tract infections acute respiratory infection (ARI) in infants at the Balangnipa Sinjai Public Health Center (Pratiwi, 2022).…”
Section: Literature Reviewmentioning
confidence: 89%
“…Another research conducted by Andi Elsa Mulya Pratiwi in 2022, it was found that the relationship history of exclusive breastfeeding with the number of the incidence of ARI in infants at the Balangnipa Sinjai Health Center using the test Chi Square obtained the probability value (p-value) Chi Square of 0.000. These results show that the probability value is <0.05, thus H0 rejected while H1 is accepted so that it is stated that there is a significant relationship between history of exclusive breastfeeding and the incidence of urinary tract infections acute respiratory infection (ARI) in infants at the Balangnipa Sinjai Public Health Center (Pratiwi, 2022).…”
Section: Literature Reviewmentioning
confidence: 89%